Budget Performance and Economic Growth in Nigeria: A Historical Review of the 4th Republic - O.S. Osadola; T. W. Ojo; S. A. Oludemi (Rowter Journal, 2023)
This paper traced and analyses how effective or not, budget has been an instrument of policy achievement in governance in Nigeria. It examines the relationship between budget performance and economic growth in Nigeria over the course of the 4th Republic (1999-2019). Budget performance in Nigeria has been characterized by both successes and challenges, including increased transparency and accountability, and efforts to invest in infrastructure and social services, as well as inadequate resource allocation, poor project planning and execution, and high levels of corruption. Economic growth in Nigeria has also been mixed over the past two decades, with a period of growth and stability in the late 1990s and early 2000s followed by a period of economic slowdown and instability due to declining oil prices and other factors. In recent years, Nigeria has made efforts to diversify its economy and has achieved some growth, but the country continues to face significant economic challenges. While it is difficult to draw a direct causal link between budget performance and economic growth, it is likely that improved budget performance, particularly in the areas of transparency, accountability, and resource allocation, could contribute to more sustainable economic growth in the country.